Millennialism in the Korean protestant church - Pak, Ŭng-gyu (Asian thought and culture, 2005)
Introduction -- Eschatology in Korean thought -- The eschatology of American missionaries to Korea -- Eschatological paradigms during the Japanese annexation, 1910-1945 -- The eschatological fight against Shintoism and its connection with premillennialism -- Eschatology and Christian life in Korea -- Conclusion